2017
DOI: 10.1108/jeim-10-2015-0099
|View full text |Cite
|
Sign up to set email alerts
|

Perceived strategic value-based adoption of Big Data Analytics in emerging economy

Abstract: Purpose The purpose of this paper is to provide an insight about factors affecting Big Data Analytics (BDA) utilization and adoption in Indian firms. Research studies have so far focused on BDA adoption in developed economies. This study examines the factors that influence BDA usage and adoption in the context of emerging economies. Design/methodology/approach This study proposed a theoretical model of factors influencing BDA utilization and adoption. Two independent research streams – first, the top manager… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
121
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(163 citation statements)
references
References 81 publications
(172 reference statements)
12
121
1
Order By: Relevance
“…With regard to the strategic orientation, our results are consistent with those of Li et al (2018) and Verma and Bhattacharyya (2017)'s findings that the major reason for the non-adoption of BDA was that companies did not realise the strategic value of BDA, and they were not ready to make changes due to technological, organisational and environmental difficulties. Therefore, we conclude that a company's strategic orientation and structure may also be important influential factors concerning the use of BDA.…”
Section: Comparison and Discussion Of The Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…With regard to the strategic orientation, our results are consistent with those of Li et al (2018) and Verma and Bhattacharyya (2017)'s findings that the major reason for the non-adoption of BDA was that companies did not realise the strategic value of BDA, and they were not ready to make changes due to technological, organisational and environmental difficulties. Therefore, we conclude that a company's strategic orientation and structure may also be important influential factors concerning the use of BDA.…”
Section: Comparison and Discussion Of The Resultssupporting
confidence: 89%
“…While prior studies (for example, Li et al, 2018) have focused on internal auditing, this paper addresses BDA and external auditors in particular. In addition, Verma and Bhattacharyya (2017) found that complexity and perceived costs were the inhibitors that prevented the adoption of BDA in business companies, while our research results indicated that the factors mentioned above were not critical. Secondly, our study examines the phenomenon of Big Data and BDA in the context of auditing.…”
Section: Contributionmentioning
confidence: 52%
“…Zhu et al (2004) for example studied e-business adoption in the finance industry applying the TOE framework in order to structure survey data from 612 firms in 10 countries [31]. Another more recent study analyzes the value-based adoption of big data analytics using the TOE framework, which is a subject area closely related to the field of AI [30]. The study outlines the main reasons for non-adoption of big data analysis, using a similar approach as our investigation.…”
Section: The Technology-organization-environment Framework (Toe)mentioning
confidence: 95%
“…Stepwise research design has been widely used in the investigation of social sciences [60][61][62], as well as in addressing marketing and organizational [63,64] aspects. Following the protocol developed in previous studies that addressed the subject topic [17,63,64], five stages of research were identified:…”
Section: Methodsmentioning
confidence: 99%